2008
DOI: 10.1007/s12033-008-9058-3
|View full text |Cite
|
Sign up to set email alerts
|

A TaqMan® Reverse Transcription Polymerase Chain Reaction (RT-PCR) In Vitro Potency Assay for Plasmid-based Vaccine Products

Abstract: A TaqMan-based reverse transcription polymerase chain reaction (RT-PCR) assay has been developed as an in vitro potency assay to measure the most immediate biological activity of plasmid DNA (pDNA)-based products. The assay measures transgene-specific messenger RNA (mRNA) from cultured cells transfected with VCL-CB01, a bivalent pDNA-based human cytomegalovirus (CMV) vaccine. The forward and reverse primers have been designed to make the RT-PCR reaction selective for plasmid-derived mRNA and to allow discrimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(26 reference statements)
0
9
0
Order By: Relevance
“…Recently, Mahajan et al (2008) reported a Taqman RT-PCR-based in vitro potency assay for DNA plasmid products and Badger et al (2011) reported the development of a flow cytometry based potency assay for a Venezuelan equine encephalitis virus DNA plasmid vaccine that assesses the in vivo expression of the transgene product in host cells. The FDA guidance document provides developers considerable flexibility in the choice of assays early in development.…”
Section: Analytical Challengesmentioning
confidence: 99%
“…Recently, Mahajan et al (2008) reported a Taqman RT-PCR-based in vitro potency assay for DNA plasmid products and Badger et al (2011) reported the development of a flow cytometry based potency assay for a Venezuelan equine encephalitis virus DNA plasmid vaccine that assesses the in vivo expression of the transgene product in host cells. The FDA guidance document provides developers considerable flexibility in the choice of assays early in development.…”
Section: Analytical Challengesmentioning
confidence: 99%
“…104 This parameter is critical since it is the only one that actually provides important information about the effi cacy of individual lots of a given plasmid biopharmaceutical. 104 This parameter is critical since it is the only one that actually provides important information about the effi cacy of individual lots of a given plasmid biopharmaceutical.…”
Section: Potency Assaysmentioning
confidence: 99%
“…104 This parameter is critical since it is the only one that actually provides important information about the effi cacy of individual lots of a given plasmid biopharmaceutical. 104 In general, potency assays will evaluate the effi ciency of gene transfer, the level and stability of expression of the encoded transgene, and its effects. 15 The existence of such assays is crucial to decide whether a specifi c production lot can be released, to check for manufacturing consistency, and to control product shelf stability.…”
Section: Potency Assaysmentioning
confidence: 99%
See 2 more Smart Citations